L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Le lock-out de La Presse et l'émeute du 29 octobre 1971: un conflit d'envergure nationale - Ménard, Yves (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Presse (La); Émeutes

L'émeute Gavazzi: violence et liberté d'expression au milieu du XIXe siècle - Breton, Vincent (Bulletin d'histoire politique, 2006)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

L’émeute Gavazzi: pouvoir et conflit religieux au Québec au milieu du 19e siècle - Breton, Vincent (Université du Québec à Montréal, 2004)
Keywords: Gavazzi, Alessandro; Irlandais; Protestants; Émeutes

The Trials and Tribulations of Riot Prosecutions: Collective Violence, State Authority and Criminal Justice in Quebec, 1841-1892 - Fyson, Donald (Canadian State Trials. Vol 3: Political Trials and Security Measures, 1840-1914, 2009)
Keywords: Criminalité; Émeutes

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

La session ardente. Fureur et violences au Parlement en 1849 - Gallichan, Gilles (Les Cahiers des Dix, 2008)
Keywords: Incendies; Parlement; Torys; Émeutes

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey, Daniel; Émeutes

Le 21 mai 1832, sur la Rue du Sang - Boileau, Gilles (Histoire Québec, 2001)
Keywords: Bagg, Stanley; Tracey, Daniel; Élections; Émeutes